Do Firms Pay Efficiency Wages? Evidence with Data at the Firm Level - Campbell, Carl M. (Journal of Labor Economics, 1993)
This study tests the efficiency wage hypothesis by estimating wage and quit equations with data from the Employment Opportunity Pilot Project survey of firms. An efficiency wage model is derived that predicts effects of turnover costs and unemployment on wages as functions of first and second derivatives from the quit equation. The model is tested by examining the relationships between the coefficients in the wage and quit equations; the results are generally favorable to efficiency wage theory. Other important findings are that firm characteristics raising workers' productivity tend to raise wages and that a rise in turnover costs reduces quits.